2018
DOI: 10.1016/j.ajpath.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Lymphangitis Precedes Colitis in Murine Norovirus–Infected Stat1-Deficient Mice

Abstract: Murine norovirus (MNV) is an RNA virus that can prove lethal in mice with impaired innate immunity. We found that MNV-4 infection of Stat1 mice was not lethal, but produced a 100% penetrant, previously undescribed lymphatic phenotype characterized by chronic-active lymphangitis with hepatitis, splenitis, and chronic cecal and colonic inflammation. Lesion pathogenesis progressed from early ileal enteritis and regional dilated lymphatics to lymphangitis, granulomatous changes in the liver and spleen, and, ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…3) . We also observed lacteal dilation, a pathology previously noted in MNV-4-infected Stat1 -/- mice 30 that can be indicative of impaired fat absorption. Overall pathology was more pronounced in the proximal half of the small intestine than the distal half, and it positively correlated with diarrhea incidence when comparing intestinal sections from pups infected with MNV-1, MNV-3, and MNV-CR6 (Fig.…”
Section: Main Textsupporting
confidence: 77%
“…3) . We also observed lacteal dilation, a pathology previously noted in MNV-4-infected Stat1 -/- mice 30 that can be indicative of impaired fat absorption. Overall pathology was more pronounced in the proximal half of the small intestine than the distal half, and it positively correlated with diarrhea incidence when comparing intestinal sections from pups infected with MNV-1, MNV-3, and MNV-CR6 (Fig.…”
Section: Main Textsupporting
confidence: 77%
“…106 Murine norovirus (MNV) is typically asymptomatic, but it induced intestinal inflammation in genetically susceptible mice. [107][108][109] In fact, MNV promoted healthy intestinal function and reversed intestinal abnormalities in germ-free mice. 68 Interestingly, MNV improved the outcome following intestinal injury through induction of IL-22 by ILC3s in an IFNα R1-and CCR2-dependent manner.…”
Section: Intracellular Pathogensmentioning
confidence: 97%
“…MNV is a single-stranded RNA virus that frequently establishes a persistent asymptomatic gastrointestinal infection in mice. Like commensal bacteria, MNV induces or exacerbates intestinal inflammation in genetically susceptible backgrounds 35 . In mice with mutation in the autophagy gene Atg16L1 , a model of the inflammatory bowel disease (IBD) Crohn’s disease, we showed that MNV infection triggers structural defects in small intestinal Paneth cells similar to patients harboring the disease-associated variant of ATG16L1 3,6 .…”
Section: Introductionmentioning
confidence: 99%